Enhancing critical analysis and problem‐solving skills in undergraduate psychology: An evaluation of a collaborative learning and problem‐based learning approach. (5th February 2013) - Karantzas, Gery C.; Avery, Michelle R.; Macfarlane, Susie; Mussap, Alexander; Tooley, Gregory; Hazelwood, Zoe; Fitness, Julie
Abstract Critical analysis and problem‐solving skills are two graduate attributes that are important in ensuring that graduates are well equipped in working across research and practice settings within the discipline of psychology. Despite the importance of these skills, few psychology undergraduate programmes have undertaken any systematic development, implementation, and evaluation of curriculum activities to foster these graduate skills. The current study reports on the development and implementation of a tutorial programme designed to enhance the critical analysis and problem‐solving skills of undergraduate psychology students. Underpinned by collaborative learning and problem‐based learning, the tutorial programme was administered to 273 third year undergraduate students in psychology. Latent Growth Curve Modelling revealed that students demonstrated a significant linear increase in self‐reported critical analysis and problem‐solving skills across the tutorial programme. The findings suggest that the development of inquiry‐based curriculum offers important opportunities for psychology undergraduates to develop critical analysis and problem‐solving skills.